ANALISIS DETERMINAN PENDAPATAN UMKM DI KABUPATEN SUMBAWA TAHUN 2010-2019 - Novi Kadewi Sumbawati; Winda Eka Apriliyanti (Jurnal Ekonomi & Bisnis, 2021)
This study aims to analyze the determinants income of Micro, Small and Medium Enterprises (UMKM) in Sumbawa district in year of 2010-2019.The type of this study was associative.The data used in this study was secondary data.The methods used to collect data were through documentation and study libraries.The data analytical tools used were t test, f test and the coefficient of determination or R2. The results of the study showed that partially there was not effect between capital and employees toward income.This was based on the value of t-count < t-table (0.622 < 2.364).Thus, Ho was accepted and Ha was rejected.Furthermore, simultaneously that there was not effect significantly between capital and employees toward income, this was based on the value of f-count < f-table (0.618 < 4.737), thus Ho was accepted and Ho was rejected.Then for the value of the coefficient of determination (R2) was of 09.3%, or 9.3% thus the percentage effect of variable x toward variable y was 9.3% while the remaining of 91.7% was affected by other variables outside this study.